Arab-Jewish activism in Israel-Palestine - Svirsky, Marcelo (Ashgate Pub., 2012)
Applying the insights of Deleuze and Guattari's works to Israel-Palestine, this title sets out to re-conceptualise the relationship between resistance and power in ethnically segregated spaces in general, and the Israeli-Palestine context in particular.